18F-FDG Positron Emission Tomography – An Innovative Technique for the Diagnosis of a Canine Lameness - Mann, Kelly; Hart, Juliette; Duerr, Felix (Frontiers in Veterinary Science, 2016)
Introduction Positron emission tomography (PET) imaging with fluorine-18-fluorodeoxyglucose (18F-FDG) is widely known for its use in the diagnosis and tracking of primary and metastatic tumors via uptake and retention of the radiopharmaceutical by hypermetabolic cells. 18F-FDG is also used to study the normal physiology of glucose uptake, metabolism, and muscle activity during and after exercise. Background A pilot study adding PET imaging to the diagnostic evaluation of canine patients undergoing computed tomography (CT) for mild or intermittent thoracic and pelvic limb lameness is ongoing. Dogs with an observable (grade 1–2/5) lameness that have undergone routine radiography and complete physical examination by board-certified veterinary surgeons and sports medicine and rehabilitation specialists are enrolled. Each patient undergoes leash walking for 15 min prior to premedication and induction of general anesthesia for the PET–CT examination. 18F-FDG is injected intravenously, and a whole-body PET examination is conducted after 1 h of radiopharmaceutical uptake time. Standard algorithm, whole-body pre- and post-contrast CT examinations, and focused, standard, and bone algorithm CT scans of the thoracic or pelvic limb areas of interest are obtained concurrently. Abnormal PET–CT findings are further investigated with additional diagnostic imaging or at surgery (e.g., ultrasound, MRI, and arthroscopy). Discussion This case report uses a canine patient referred for thoracic limb lameness to illustrate the role of advanced imaging in a diagnostic plan and to discuss a recommended PET–CT procedure for lameness evaluation. The PET–CT imaging protocol recommended in this report was designed to significantly enhance a routine thoracic limb CT examination and to identify areas of muscle, tendon, or ligament overuse, inflammation, or injury for further diagnostic procedures or definitive treatment. Concluding remarks 18F-FDG PET–CT adds valuable physiologic and anatomic information to the diagnostic evaluation of patients presenting with indistinct or intermittent clinical signs of musculoskeletal inflammation or injury. In addition, tailoring the PET acquisition and radiopharmaceutical parameters allows for detailed information gathering to more closely assess normal and abnormal physiology, unlocking a new frontier in the study of canine athletic injury and optimal performance.